2013
DOI: 10.1155/2013/562643
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Provision of ENT Health Care Service at Primary and Secondary Hospital Level in a Developing Country

Abstract: ENT problems are the most common reason for a visit to a doctor in both rural and urban communities. In many developing countries, there is a lack of ENT specialists and overburdened hospital facilities. To date, there is no comprehensive study that has evaluated the spectrum of ENT disorders in a rural community. Methods. A prospective study was done for a period of three years to profile the cases presenting to the outpatient clinic in a secondary care hospital and in the camps conducted in tribal areas in V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 14 publications
2
43
2
Order By: Relevance
“…This is in accordance with a study by Das et al where most frequent age group was 21-30 (20.82%), followed by 11-20 and 31-40 age group, [11] as young age group is most common age group to seek medical advice in ENT field. [12,13] It was noticed in our study that first four decades accounted for 73.25% of total which is quite close to that of Mina et al; 72.59%. [10] In our study, maximum patients had attended ENT OPD for throat and neck complaints, followed by ear diseases and least with nasal disorder.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in accordance with a study by Das et al where most frequent age group was 21-30 (20.82%), followed by 11-20 and 31-40 age group, [11] as young age group is most common age group to seek medical advice in ENT field. [12,13] It was noticed in our study that first four decades accounted for 73.25% of total which is quite close to that of Mina et al; 72.59%. [10] In our study, maximum patients had attended ENT OPD for throat and neck complaints, followed by ear diseases and least with nasal disorder.…”
Section: Discussionsupporting
confidence: 90%
“…In other studies also it was noted that allergic rhinitis is most upcoming disease. [13] Due to increase in pollution allergic rhinitis and its comorbidities are on rising trend. Next was DNS which has been reported as most common diagnosis by Mina et al in their study.…”
Section: Discussionmentioning
confidence: 99%
“…5 The age of onset of AOM is indirectly proportional to the chronicity of the disease; that is, early onset of AOM predisposes to chronic otitis media. 9 But, in our study CSOM was more common among the age-group 5-9 yrs. This may be due to one of the limitations of the study that all the patients, whether new or follow-up patients were included in the study.…”
Section: Discussioncontrasting
confidence: 59%
“…It is the most common cause of persistent mild to moderate hearing impairement and more commonly found in children of government school and rural areas. 7 Second most common ear disorder reported was OME 11.7% and 3 rd 9 Rijal et al reported AOM as most common ear disorder after wax. 5 Our study is different from other similar studies in that we attempted to see associations between three agegroups (0-4 yrs, 5-9 yrs, 10-16 yrs) and ENT disorders.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition to the economic impact of hearing loss at an individual level, hearing loss substantially affects social and economic development in communities and countries so interventions in the form of trained community health staff could be an effective way for improving the access for rural community for health care services specific to ear problems. 12 As the prevalence of hearing impairment was higher among elderly, specific need based interventions for this population can be provided.…”
Section: Discussionmentioning
confidence: 99%